Clinicopathological Profile of Rhabdomyosarcoma in Children - Begum, Umme Habiba; Islam, Afiqul (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Objectives: To describe the clinical profile as well as histopathological sub-types of Rhabdomyosarcoma in children. Methods: A hospital base prospective observational study was conducted among 20 diagnosed cases of Rhabdomyosarcoma in children, those attending in Hemato-Oncology department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in the period between January to December 2009. Results: The peak incidence of Rhabdomyosarcoma was in 1-5 years of age group (n=9, 45%) with mean age 6.83 years with male to female ratio 5.66:1. The common sites of primary tumor was in head and neck region (40%, n=08), followed by genito-urinary tract, 30% (n=06), extremities 20% (n=04), trunk 10% (n=02). The most common clinical presentation was mass lesion 100% (n=20), followed by local pain 25% (n=05), urinary obstructions 15% (n=03) dysphagia, chronic otorrhea, dysuria, haematuria, and proptoses were 10% each (n=02, each); The histological sub-types were Embryonal 60% (n=12), alveolar 30% (n=6), and Botryoid 10% (n=02); Of Embryonal variety in head and neck region 58.33% (n=7), and Genito-urinary sites 41.67% (n=5); of Alveolar variety in trunk 66.67% (n=4), and in extremities33.33% (n=2), of Botryoid sub-type frequency was equal in head - neck region and genitourinary site 50% each (n=1). Conclusion: Children with Rhabdomyosarcoma presented mostly in 1 to 5 years of age, with mass lesion (100%), predominantly in head and neck region (40%) and the commonest histological sub-type was Embryonal variety (60%). DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12461 J Bangladesh Coll Phys Surg 2012; 30: 132-136